Should we change the cannulation site for right subclavian artery cannulation? An experimental study with a newly designed cannula. (November 2016) - Cakir, Habib; Kestelli, Mert; Yurekli, Ismail; Eygi, Bortecin; Iscan, Sahin; Isık, Yasemin; Aşar, Kamil; Ogut, Hasan
Background: In this experimental study, we primarily aimed to show the hemodynamic effects and superiority of this newly designed cannula for perfusion compared to standard subclavian cannulation. The new cannula (Figure 1) allows bidirectional axial flow and it directly fits in the brachiocephalic trunk (innominate artery). Methods: We used a cardiopulmonary bypass roller pump, reservoir, 3/8- 1/2- 1/4-inch Y-connectors and tubing set. Lines were set as seen in Figures 2, 3, 4 and 5. The anatomy of the aorta (ascending, arch, branches, descending) was mimicked, using tubing sets with different sizes and the connectors yielding similar angles and configurations. In this experimental vascular system, systemic vascular resistance was created with partial clamping of the common tubing set. The cannulation sites were created in the subclavian artery and the innominate artery. Perfusion was established with the same pump rate and the same occlusion pressures (systemic vascular resistance). The pressure readings were obtained in the right carotid artery, the left carotid artery and the left subclavian artery. Results: These experimental models of vasculature allowed us to measure pressures in the carotid system for different cannulation set-ups, using both our newly designed double-outflow cannula, which was introduced via the innominate artery, and the standard arterial cannula, which was introduced via the subclavian artery. Higher pressure recordings were obtained in the carotid system with the new cannula introduced through innominate artery. Conclusion: Higher cerebral perfusion readings were obtained with our newly designed bidirectional cannula introduced via the innominate artery compared to standard cannulation through the right subclavian artery.